Heavy metal [videorecording (DVD)] - Potterton, Gerald, 1931-; Bumpass, Rodger; Candy, John; Francks, Don, 1932-2016; Fagen, Donald, 1948-; Felder, Don; Hagar, Sammy; Nicks, Stevie (Columbia TriStar Home Video, 1999)
An otherworldly tale of a glowing green orb from outer space that spreads destruction throughout the galaxy. Only when it encounters its one true enemy will goodness prevail in the universe.